Older people's forums in the United Kingdom: civic engagement and activism reviewed. Issue 3 (12th September 2016) - Manthorpe, Jill; Harris, Jess; Mauger, Sam
Abstract : Purpose: The purpose of this paper is to review the literature on UK older people's forums. Forums seek to influence statutory responses to ageing, and enable older people to speak up on matters important to them. The review examined three facets of forums: their membership, structures, and effectiveness. Design/methodology/approach: Methods included searching databases, internet, and specialist libraries for materials relating to older people's forums. Key points were extracted and source material described but not subject to quality appraisal. Relevant non-UK studies are included to draw contrast and comparisons. Findings: Several studies and reports have explored forum members' socio-demographic profiles, motivations and triggers for joining and the two-way rewards of participation. However, membership remains a minority activity, with only a small percentage of members actively engaged and the review highlights gaps in the literature on widening participation. Both statutory and voluntary sectors have supported forum development and sustainability. There is little data on formal structures but some exploration of the informal communications and behaviours that sustain them has been undertaken. Forums are viewed as effective but resource intensive. The size and representativeness of the membership, strength of influence and deployment of members' expertise are all identified as potential contributors to effectiveness. Research limitations/implications: Some material may not have been accessible and there is potential bias by greater inclusion of journal published materials than other possible sources. Material was not quality appraised, and research literature and self-reporting by forums are presented alongside each other. Practical implications: Practitioners should familiarise themselves with current older people's organisations locally to ensure that consultations are broad and reach different groups. While partnerships with voluntary sector health and care providers are encouraged some of these groups may not wish to represent all older people. Wider reach may provide multiple perspectives. Help in kind as well as financial resources may be welcomed by older people's groups, such as meeting spaces, assistance with administration, and briefings that are accessible. Offering to meet with older people's forums to discuss matters regularly may provide insight into experiences of services and changing needs earlier than professional feedback. Dismissing older people's forums as made up of the "usual suspects" is likely to be unfair and unhelpful to building up positive relationships. Originality/value: The review provides a preliminary assessment of the size and scope of research and grey literature on UK older people's forums, synthesising points of similarity and difference and identifying clear gaps in the evidence.